PENGARUH DANA OTONOMI KHUSUS, PENDAPATAN ASLI DAERAH DAN DANA PERIMBANGAN TERHADAP KESEJAHTERAAN MASYARAKAT - Boky, Novita (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
In Indonesia, the fiscal decentralization policy is provided by the central government in the form of balancing fund, special-autonomy fund, and adjustment funds, as well as in the form of instruments that can increase the potential for local own-source revenue with the aim of equitable development and increasing people's welfare. Transfer funds from the central government can have an impact on people's welfare if the funds are allocated to programs/activities that can improve public services. This study aims to determine the effect of special-autonomy fund, local own-source revenue and balancing fund on people's welfare as measured using the human development index (HDI) in West Papua Province. This study uses panel data regression, using explanatory research. The results of this study indicate that special-autonomy fund and balancing fund have a positive and significant effect on the human development index (HDI) , while local own-source revenue has a positive but not significant effect.